2013
DOI: 10.1016/j.pain.2013.03.028
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of a glial inhibitor, minocycline, for preventing persistent pain after lumbar discectomy: A randomized, double-blind, controlled study

Abstract: Minocycline strongly inhibits microglial activation, which contributes to central sensitization, a major mechanism underlying chronic pain development. We hypothesized that the perioperative administration of minocycline might decrease persistent pain after lumbar discectomy. We randomly assigned 100 patients undergoing scheduled lumbar discectomy to placebo and minocycline groups. The minocycline group received 100mg minocycline orally, twice daily, beginning the evening before surgery and continuing for 8 da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(46 citation statements)
references
References 52 publications
2
42
0
2
Order By: Relevance
“…Five of the nine studies examined local anesthetics in several surgical populations [12][13][14][15][16], one study compared a tumor necrosis factor-alpha (TNF-a) inhibitor (i.e., enteracept) for inguinal hernia compared to placebo [17], another study compared pregabalin versus placebo in a cardiac surgery model [18], and another study examined minocycline (a broad-spectrum cycline antibiotic which has been shown to block microglial activation) compared to placebo following lumbar discectomy [19]. These eight trials were negative and did not demonstrate a preventive analgesic effect [12][13][14][15][16][17][18][19]. Only one of the nine studies identified in our updated literature search found a preventive effect on the incidence of CPSP [20].…”
Section: Search Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Five of the nine studies examined local anesthetics in several surgical populations [12][13][14][15][16], one study compared a tumor necrosis factor-alpha (TNF-a) inhibitor (i.e., enteracept) for inguinal hernia compared to placebo [17], another study compared pregabalin versus placebo in a cardiac surgery model [18], and another study examined minocycline (a broad-spectrum cycline antibiotic which has been shown to block microglial activation) compared to placebo following lumbar discectomy [19]. These eight trials were negative and did not demonstrate a preventive analgesic effect [12][13][14][15][16][17][18][19]. Only one of the nine studies identified in our updated literature search found a preventive effect on the incidence of CPSP [20].…”
Section: Search Resultsmentioning
confidence: 99%
“…The heterogeneity with respect to the timing of interventions, the time points studied, and the outcomes assessed limit meaningful comparison of CPSP trials to date .There were two negative trails identified in this review which focused on minocycline [19] and entanercept [17] as possible agents that may play a role in modifying the transition from an acute pain to chronic pain. The role of tumor necrosis factor-alpha (TNF-a) inhibitors and medications implicated in the blocking of microglial activation deserve further study.…”
Section: Future Directionsmentioning
confidence: 99%
“…36 A recent example of attempts to prevent chronic pain with a ''non-analgesic'' intervention comes from a placebo-controlled trial of oral minocyclinean inhibitor of microglial activation expected to suppress central sensitization -administered for eight days perioperatively in lumbar discectomy patients. 37 Unfortunately, minocycline did not produce significant pain reductions at three months postoperatively; however, since all patients had pain prior to surgery, it must be acknowledged that this trial was conducted in likely the most challenging population for prevention. 37 It is possible that such neuroprotective agents may show even more impressive preventive efficacy when administered perioperatively to patients with no preexisting pain.…”
Section: Is It Time For a Different Prevention Paradigm?mentioning
confidence: 93%
“…37 Unfortunately, minocycline did not produce significant pain reductions at three months postoperatively; however, since all patients had pain prior to surgery, it must be acknowledged that this trial was conducted in likely the most challenging population for prevention. 37 It is possible that such neuroprotective agents may show even more impressive preventive efficacy when administered perioperatively to patients with no preexisting pain. These concepts provide new opportunities for research and treatment with different classes of potentially preventive interventions.…”
Section: Is It Time For a Different Prevention Paradigm?mentioning
confidence: 93%
See 1 more Smart Citation